INFLASI, HARGA EMAS, JUMLAH NASABAH, PENDAPATAN USAHA, DAN PENYALURAN PEMBIAYAAN RAHN - Bilqis Nabilah; Mira Rahmi (Fakultas Ekonomi Dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2023)
The development of Rahn's financing distribution is still quite low compared to KCA financing at PT. Pegadaian. Of course there are internal and external factors that will affect the amount of the financing distribution. The purpose of this study was to analyze the effect of inflation, gold prices, number of customers, and operating income on the distribution of Rahn's financing at PT. Pegadaian period 2016-2020. Quantitative research approach with secondary data using multiple linear regression analysis method. The results of this study are the influence of the independent variables simultaneously on the distribution of Rahn's financing. However, in a partial test, only the Gold Price, Number of Customers, and Operating Income factors have a significant influence on the distribution of Rahn's financing, while the inflation factor does not have a significant effect on the distribution of Rahn's financing. The results of this study are expected to provide benefits based on existing information in order to design new strategies, so that the distribution of Rahn increases Keywords: Gold Price; Inflation; Number of Customers; Operating Income; Rahn